SISTEM INFORMASI PELAYANAN RUMAH SAKIT PADA RUMAH SAKIT UMUM CHASAN BOESOIRIE MALUKU UTARA BERBASIS CLIENT SERVER - Rasai, Dafik M; Sutanta, Edhy; Hamzah, Amir (Jurnal Script, 2014)
ABSTRACTInformation system service general hospital chasan boesoirie is a computerized system management data, service, and reports and information that function to management data income information pertaining to the hospital.Information system service general hospital chasan boesoirie having ability connection database based client server.Information system service general hospital chasan boesoirie aims to do information management relating to by dept. the hospital, including service examination patients, handling ambulatory, inpatient, administering. until the administration of finance the hospital.Information system service general hospital chasan besoirie assembled programming language delphi 7.0 with mysql.More possessed by this system is completeness report that can be displayed in detail with copy that deals with the hospital services in general hospital chasan boesoirieKeyword : client/server, information systems hospital. Delphi 7.0, MySQL